2017
DOI: 10.1021/acsomega.7b00672
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of Low-Dimensional Silver Nanoclusters with Their Tunable Plasmonic and Thermodynamic Behavior

Abstract: Optical properties of noble metal nanostructures associated with localized surface plasmon resonance (SPR) are technically important for optical switches and plasmonic devices. In this work, silver nanoclusters are embedded inside the soda-lime glass matrix, followed by a thermal annealing process in an open air atmosphere for 1 h. The effects of thermal annealing on the plasmonic behavior of Ag nanoclusters embedded in the glass matrix are studied with UV–vis spectroscopy and photoluminescence. In the SPR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…15). The ∆H values revealed the reduction process of reduced Cu atoms through a redox while ∆S helps to understand the Cu NPs reorientation mechanism which was reported in our previous work 44 . These two thermodynamic parameters collectively have inferred thermal growth and accumulation behaviour which utilize almost all the energy in a process to balance a minimum energy.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…15). The ∆H values revealed the reduction process of reduced Cu atoms through a redox while ∆S helps to understand the Cu NPs reorientation mechanism which was reported in our previous work 44 . These two thermodynamic parameters collectively have inferred thermal growth and accumulation behaviour which utilize almost all the energy in a process to balance a minimum energy.…”
Section: Resultssupporting
confidence: 64%
“…These two thermodynamic parameters collectively have inferred thermal growth and accumulation behaviour which utilize almost all the energy in a process to balance a minimum energy. Spontaneity of any chemical reaction could be represented by Δ G values 45 and thus, we have explained a dependence of Δ G in favour of Cu NPs formation within dielectric matrix. During the growth and nucleation of Cu atoms, a decrease in Δ G value is observed with an increase in annealing temperatures.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It must be pointed out that the calculated clusters sizes obtained from FEGTEM are smaller than the crystallite size as calculated from using the Scherrer formula and the XRD patterns. Inwati et al have recently reported a similar trend of crystalline size difference as estimated from XRD which was also not consistent with the size estimated from FEGTEM. This may be attributed to the effect of crystal breakage due to crushing of the silver embedded glass into the fine powder, which has been used for the FEGTEM measurements.…”
Section: Resultsmentioning
confidence: 78%
“…The transformation of the Ag + ions to Ag 0 neutral atoms under thermal treatments, are explained below where the glass impurities provides the necessary electrons to reduce the Ag + → Ag 0 (Scheme ) …”
Section: Resultsmentioning
confidence: 99%